Транскордонний туризм як засіб міжкультурної взаємодії України і Польщі (на прикладі Чернівецької області) - Бучко, Жанна Іванівна; Меленко, Яна Іллівна (Івано-Франківськ, 2015)
В статті досліджено тенденції міжкультурної взаємодії транскордонного співробітництва України та Польщі в галузі туризму. Визначено процеси міжкультурної комунікації через аналіз програм транскордонних проектів та результатів їх реалізації в аспекті українсько-польської туристичної співпраці. На прикладі транскордонних проектів, що реалізовувалися протягом останніх 20-ти років, виявлено їх вплив на сталий розвиток туризму в Чернівецькій області. Визначено ряд культурних подій та заходів, що сприяють міжкультурній комунікації в галузі польсько-українського туризму.
Cross-border tourism as a means of intercultural communication Ukraine and Poland (for example, Chernivtsi region)
The investigation of a cross-border transaction intercultural communication tendencies between Poland and Ukraine in the field of tourism is studied in this paper. Through the Polish and Ukrainian cooperation in the sphere of tourism an international communication and a cross-border tourism are analyzed: tourism flows, realization of cross-border projects, institutional tourism providing in the aspect of polish-ukrainian tourism cooperation. Here are determined main obstacles, prospects and advantages of a cross-border cooperation between Poland and Ukraine in the tourism realm at present time. The processes of intercultural communication through the analysis of cross-border projects and the results of their implementation in terms of Ukrainian-Polish tourism cooperation was defined. The example of cross-border projects that were implemented over the last 20 years, their impact on the sustainable development of tourism in the Chernivtsi region was revealed. A number of cultural events and activities that promote intercultural communication in the Polish-Ukrainian tourism was defined. The scientific novelty of work consists in the analysis of features and tendencies of problems and prospects of development of transfrontal collaboration in the aspect of cross-cultural tourist communication. The research and practice value of research consists in the informative accumulation of data in relation to a українсько-польської transfrontal collaboration in the sphere of cross-cultural tourist communication, in forming of suggestions in relation to the programs of development of tourism in Ukraine with the aim of establishment of the stable Polish-Ukraine collaboration.
Keywords: Транскордонний туризм; транскордонна співпраця; транскордонний проєкт; Єврорегіон; міжкультурна комунікація